2021
DOI: 10.3389/fonc.2021.645686
|View full text |Cite
|
Sign up to set email alerts
|

The Dual-Role of Methylglyoxal in Tumor Progression – Novel Therapeutic Approaches

Abstract: One of the hallmarks of cancer cells is their metabolic reprogramming, which includes the preference for the use of anaerobic glycolysis to produce energy, even in presence of normal oxygen levels. This phenomenon, known as “Warburg effect”, leads to the increased production of reactive intermediates. Among these Methylglyoxal (MGO), a reactive dicarbonyl known as the major precursor of the advanced glycated end products (AGEs), is attracting great attention. It has been well established that endogenous MGO le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“… Archaeal metabolites and their potential roles with various cancers. Relations were organized and displayed on the basis of previous reports ( 7 , 40 42 , 61 , 87 89 ). …”
Section: Discussionmentioning
confidence: 99%
“… Archaeal metabolites and their potential roles with various cancers. Relations were organized and displayed on the basis of previous reports ( 7 , 40 42 , 61 , 87 89 ). …”
Section: Discussionmentioning
confidence: 99%
“…MGO accumulation can promote inflammation and contribute to endothelial dysfunction. The dual-role of MGO in tumor progression and its anti-cancer effect was initially attributed to MGO cytotoxicity, and its subsequent pro-tumorigenic effect was observed in several types of cancer, including CRC [38]. Normal cells use mitochondrial oxidative respiration with oxygen availability to produce energy.…”
Section: Discussionmentioning
confidence: 99%
“…MGO irreversibly modifies an estimated 1 to 5% of proteins at arginine residues, forming the MGO-derived argpyrimidine [115] and hydroimidazolone [116] AGEs. The accumulated evidence suggests that MGO-modified proteins connect diabetes with cancer [117] and are associated with several cancers [118]. By silencing the detoxication of MGO by glyoxalase 1, it was reported that MGO favored nuclear localization of the transcriptional coactivator YAP (Yes-associated protein) [119] and inactivation of the Hippo tumor suppressor pathway [120] in breast cancer cells, thereby promoting proliferation [121].…”
Section: Methylglyoxalmentioning
confidence: 99%